Educar la mirada desde la representación - Palacios, José Antonio (2018)
Is visual literacy at the height of visual culture? Does it adapt to a world of screens and images? Our life is traversed by images of all kinds. Mobile phones, for example, lead to a communicative "obsession". This makes it difficult to analyze the visual image. To see is not to believe but to interpret. Visual images succeed or fail as long as we can interpret them. The student must read the images that surround him, understand them and process them, for their representation. Figures and simple volumes will lead to unexpected material / immaterial spaces.